Benefits of a Circular Economy in the context of Resources and Waste Management in Poland and the EU - Ewa BIEŃ (Communications of International Proceedings, 2021)
A circular economy (CE) is a model of an optimistic economy with a vision of a better future. It refers to every country that thinks globally about the world in which we live. Significant environmental burdens related to accelerating global warming and resource scarcity cause many countries to seek innovative approaches to mitigate this phenomenon. A response to that is the Green Deal, and within it, a circular economy as one of climate-related sector areas. The aim of this paper is to point out the current problems in the implementation of a circular economy in the EU countries, as well as the concrete benefits of implementing the circular economy principles from the perspective of proper waste management. Based on analysis of available literature, collected data and based on selected indicators of a circular economy, the progress of the implementation of the actions towards a circular economy in the European Union over recent years was assessed. The conclusions drawn from the analysis of data, for the European Union overall, are not satisfactory. In the analysed period, many EU countries showed significant changes in the values of the indicators used to assess the transformation towards a circular economy. They included, among other things, Holland, Belgium, France and Italy, implying environmental, social and economic benefits in these countries. However, in many EU countries, a lot still remains to be done. It should be noted that Poland is just at the beginning of the transformation path, as many other EU countries are. Analysis of the data showed, among other things, that in 2018 as many as 16 EU countries had a much lower circular material use rate than Poland.
Keywords: Circular Economy (CE); Management; Resources; Waste Management.